Adverse Childhood Experiences and Rate of Memory Decline From Mid to Later Life: Evidence From the English Longitudinal Study of Ageing. Issue 7 (4th February 2021) - O'Shea, Brendan Q; Demakakos, Panayotes; Cadar, Dorina; Kobayashi, Lindsay C
Abstract: Evidence on the role of early-life adversity in later-life memory decline is conflicting. We investigated the relationships between adverse childhood experiences (ACEs) and memory performance and rate of decline over a 10-year follow-up among middle-aged and older adults in England. Data were from biennial interviews with 5, 223 participants aged 54 years or older in the population-representative English Longitudinal Study of Ageing from 2006/2007 to 2016/2017. We examined self-reports of 9 ACEs prior to age 16 years that related to abuse, household dysfunction, and separation from family. Memory was assessed at each time point as immediate and delayed recall of 10 words. Using linear mixed-effects models with person-specific random intercepts and slopes and adjusted for baseline age, participants' baseline age squared, sex, ethnicity, and childhood socioeconomic factors, we observed that most individual and cumulative ACE exposures had null to weakly negative associations with memory function and rate of decline over the 10-year follow-up. Having lived in residential or foster care was associated with lower baseline memory (adjusted β = −0.124 standard deviation units; 95% confidence interval: −0.273, −0.025) but not memory decline. Our findings suggest potential long-term impacts of residential or foster care on memory and highlight the need for accurate and detailed exposure measures when studying ACEs in relation to later-life cognitive outcomes.